2018
DOI: 10.1097/qai.0000000000001726
|View full text |Cite
|
Sign up to set email alerts
|

Using a Social Network Strategy to Distribute HIV Self-Test Kits to African American and Latino MSM

Abstract: Findings suggest that a network-based strategy for self-test distribution is a promising intervention to increase testing uptake and reduce undiagnosed infections among AAMSM and LMSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 26 publications
6
107
1
1
Order By: Relevance
“…To our knowledge, this is one of the first studies in sub-Saharan Africa to evaluate secondary distribution of HIVST by MSM peers to their social and sexual networks. Our findings suggest that distributing HIVST kits through peer networks is feasible, acceptable and could be an effective strategy to increase uptake of HIV testing and linkage to care in a marginalized and stigmatized population with low testing coverage [8][9][10][11][12][13][14][15]. Our results are in agreement with prior studies done among heterosexual fishing communities in Uganda, and MSM in the United Kingdom and United States, in which peer distribution of HIVST had high uptake and acceptability and successfully identified undiagnosed HIV infections [13,18,30,31].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To our knowledge, this is one of the first studies in sub-Saharan Africa to evaluate secondary distribution of HIVST by MSM peers to their social and sexual networks. Our findings suggest that distributing HIVST kits through peer networks is feasible, acceptable and could be an effective strategy to increase uptake of HIV testing and linkage to care in a marginalized and stigmatized population with low testing coverage [8][9][10][11][12][13][14][15]. Our results are in agreement with prior studies done among heterosexual fishing communities in Uganda, and MSM in the United Kingdom and United States, in which peer distribution of HIVST had high uptake and acceptability and successfully identified undiagnosed HIV infections [13,18,30,31].…”
Section: Discussionsupporting
confidence: 89%
“…Community-based HIV self-testing delivered by members of a target community or social group could be more effective in reaching those who may not seek testing in high-stigma contexts [20,32]. This approach builds on prior experiences of peer-driven distribution of HIV prevention tools and referral coupons for HIV testing in key populations, e.g., coupon distribution among MSM in Uganda [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary advantages of network-based strategies include: 1) network members have access to broader networks of MSM who may not access prevention programs or services due to concerns of confidentiality or negative experiences with providers; 2) network members can also access their networks outside clinic hours and in venues often not accessible to traditional outreach workers, overcoming some logistical barriers; and 3) being reached and encouraged to test by peers in their own network whom they trust may alleviate the negative impact of HIV-and gay-related stigma on testing behaviors. In a feasibility study conducted among African American and Latinx MSM in California, it was reported that compared to a local county testing program, the peer-based strategy to distribute HIVST kits through MSM's social and sexual networks was significantly more likely to reach those who have never tested for HIV and those who were previously undiagnosed [20]. The objectives of this study were to examine patterns and correlates of HIVST distribution within Chinese MSM's sexual networks.…”
Section: Plos Onementioning
confidence: 99%